The co-responsibility of mass and environment in the formation of lenticular galaxies. Issue Volume 15:Issue S359(2020) (March 2019) - Cortesi, A.; Coccato, L.; Buzzo, M. L.; Menéndez-Delmestre, K.; Goncalves, T.; Mendes de Oliveira, C.; Merrifield, M.; Arnaboldi, M.
Abstract: We present the latest data release of the Planetary Nebulae Spectrograph Survey (PNS) of ten lenticular galaxies and two spiral galaxies. With this data set we are able to recover the galaxies' kinematics out to several effective radii. We use a maximum likelihood method to decompose the disk and spheroid kinematics and we compare it with the kinematics of spiral and elliptical galaxies. We build the Tully- Fisher (TF) relation for these galaxies and we compare with data from the literature and simulations. We find that the disks of lenticular galaxies are hotter than the disks of spiral galaxies at low redshifts, but still dominated by rotation velocity. The mechanism responsible for the formation of these lenticular galaxies is neither major mergers, nor a gentle quenching driven by stripping or Active Galactic Nuclei (AGN) feedback.